# Calculator search results

Formula
Solve the equation
Graph
$y = \dfrac { x - 3 } { 10 }$
$y = \dfrac { x + 3 } { 4 }$
$x$-intercept
$\left ( 3 , 0 \right )$
$y$-intercept
$\left ( 0 , - \dfrac { 3 } { 10 } \right )$
$x$-intercept
$\left ( - 3 , 0 \right )$
$y$-intercept
$\left ( 0 , \dfrac { 3 } { 4 } \right )$
$\dfrac{ x-3 }{ 10 } = \dfrac{ x+3 }{ 4 }$
$x = - 7$
 Solve a solution to $x$
$\color{#FF6800}{ \dfrac { x - 3 } { 10 } } = \color{#FF6800}{ \dfrac { x + 3 } { 4 } }$
 Multiply both sides by the least common multiple for the denominators to eliminate the fraction 
$\color{#FF6800}{ 2 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \right ) = \color{#FF6800}{ 5 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 15 }$
$\color{#FF6800}{ 2 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \right ) = 5 x + 15$
 Multiply each term in parentheses by $2$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 3 } \right ) = 5 x + 15$
$2 x + \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 3 } \right ) = 5 x + 15$
 Multiply $2$ and $- 3$
$2 x \color{#FF6800}{ - } \color{#FF6800}{ 6 } = 5 x + 15$
$2 x - 6 = \color{#FF6800}{ 5 } \color{#FF6800}{ x } + 15$
 Move the variable to the left-hand side and change the symbol 
$2 x - 6 \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ x } = 15$
$2 x \color{#FF6800}{ - } \color{#FF6800}{ 6 } - 5 x = 15$
 Move the constant to the right side and change the sign 
$2 x - 5 x = 15 \color{#FF6800}{ + } \color{#FF6800}{ 6 }$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ x } = 15 + 6$
 Organize the expression 
$\color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = 15 + 6$
$- 3 x = \color{#FF6800}{ 15 } \color{#FF6800}{ + } \color{#FF6800}{ 6 }$
 Add $15$ and $6$
$- 3 x = \color{#FF6800}{ 21 }$
$\color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = \color{#FF6800}{ 21 }$
 Change the sign of both sides of the equation 
$3 x = - 21$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 21 }$
 Divide both sides by the same number 
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 7 }$
 그래프 보기 
Graph
Solution search results